Program Sosialisasi Keamanan Email Akademik Mahasiswa Terhadap Ancaman Phishing Berbasis Social Engineering - Sentosa Pohan; Hafizhah Mardivta2; Riswan Syahputra Damanik (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2023)
The rapid development of digital technology has brought significant benefits to the field of education, particularly through the use of academic email as an official medium of communication. However, this also creates potential security risks, especially phishing attacks based on social engineering. The low level of digital security literacy among students makes academic email accounts vulnerable to cybercrime. This study aims to implement an awareness program on academic email security, focusing on improving students’ understanding of phishing threats at SMA Islam Terpadu Rantau Prapat. The method used was an interactive workshop approach, which included theoretical sessions, demonstrations of phishing cases, simulations on identifying fake emails, and group discussions. Evaluation was carried out through pre-tests and post-tests to measure the participants’ ability to detect phishing. The results showed a significant improvement in students’ knowledge and skills, with the percentage of participants able to identify phishing increasing from 20% before the program to 82% after the program. These findings demonstrate that practice-based education is effective in building students’ digital literacy. The limitation of this study lies in the relatively small sample size and short-term evaluation. Future research is expected to expand the number of participants and integrate interactive technologies to ensure more sustainable impacts.